Association of Umbilical Coiling Index in Normal And Complicated Pregnanc - Mustafa , Snoor Jalal; Said , Abir Moheidin (Diyala Journal of Medicine, 2019)
Background: Umbilical cord index is the total number of coils divided by the total length of the umbilical cord in centimeters and an abnormal umbilical coiling index has been reported to be related to adverse fetal and pregnancy outcomes. Objective: To compare and detect the association of the umbilical coiling index in normal and complicated pregnancies. Patients and Method: This study was conducted in Sulaimania city in both Sulaimania Maternity Hospital and Soma Private Hospital from July 2012 to May 2013.A total number of 428 umbilical cords were examined, umbilical coiling index (UCI) was calculated by dividing the total number of coils by the umbilical cord length in centimeters. The outcomes measured were maternal age, intrauterine growth retardation, meconium staining, birth weight, apgar score,maternal diabetes mellitus and pregnancy induced hypertension. Hypocoiled cords were those having UCI less than 10th centile, and hypercoiled cords those having UCI more than 90th centile. Statistical analysis was done by chi square test, Fishers exact test and the t test where applicable. Results: The mean UCI was 0.24±0.003 coils per one cm, hypocoiled cords were significantly associated with complicated pregnancies by pregnancy induced hypertension (PIH), gestational diabetes mellitus (GDM), and oligohydromnios (p value<0.05), while hypercoiled cords were associated with maternal age >35 years, (GDM), oligohydromnios, and polyhydromnios. Significant association detected regarding the cesarean section with hypercoiled cord, abnormal fetal heart AFH, meconium stained liquor (MSL), low Apgar score at 5 min. and low birth weight (LBW) were significantly associated with both hypo and hypercoiled cords (p-value <0.05). Conclusions: Abnormal UCI is associated with several adverse antenatal, perinatal, and neonatal factors, and UCI is an indicator and marker for pregnancy and fetal outcomes.